BIBLIOMETRIC ANALYSIS AND RESEARCH TRENDS ON MICROPLASTIC POLLUTION IN THE SOIL AND TERRESTRIAL ECOSYSTEMS - VIRÚ-VÁSQUEZ, PAUL (2024)
ENVIRONMENTAL POLLUTION FROM MICROPLASTICS (MPS), AN ANTHROPOGENICALLY MEDIATED MENACE TO THE BIOSPHERE, IS A GLOBAL CONCERN. THIS RESEARCH CONDUCTED A BIBLIOMETRIC ANALYSIS OF MPS IN SOIL AND TERRESTRIAL ECOSYSTEMS USING R SOFTWARE AND BIBLIOSHINY TO ANALYZE DESCRIPTIVE STATISTICS, AUTHOR CONTRIBUTIONS, DOCUMENTS, AND CONCEPTUAL STRUC-TURES. THE SCOPUS DATABASE WAS SELECTED, AND VARIOUS KEYWORDS OPTIMIZED THE SEARCH. AN ANALYSIS OF RESEARCH TRENDS DIVIDED THE TIMELINE INTO THREE PERIODS: PERIOD I (2012–2018), PERIOD II (2019–2021), AND PERIOD III (2022). RESULTS SHOWED WANG J. AS THE AUTHOR WITH THE HIGHEST H-INDEX, WHILE SCIENCE OF THE TOTAL ENVIRONMENT HAD AN H-INDEX OF 43. IN PERIOD I, RESEARCH FOCUSED ON MPS AND PLASTIC POLLUTION, RAISING QUESTIONS ABOUT THEIR IMPACTS ON TERRESTRIAL ECOSYSTEMS. RESEARCH FOUND THAT MPS NEGATIVELY AFFECTED SOIL ORGANISMS BY DECREASING GROWTH RATES AND CAUSING WEIGHT LOSS. IN PERIOD II, RESEARCH DIVERSIFIED, EXPLORING INTERACTIONS BETWEEN MPS AND HEAVY METALS, BIOACCUMULATION, PHYTOTOXICITY, SOIL POLLUTION, AND GUT MICROBIOTA. RESEARCH REVEALED THAT MPS COULD INFLUENCE HEAVY METAL UPTAKE BY PLANTS AND AFFECT BACTERIAL COMMUNITY STRUCTURES IN SOIL. IN PERIOD III, RESEARCH EMPHASIZED OXIDATIVE STRESS, A COMMON ECOTOXICITY RESPONSE IN PLANTS AND ANIMALS. MPS INDUCED OXIDATIVE STRESS, LEADING TO REACTIVE OXYGEN SPECIES (ROS) BUILDUP. POLYETHYLENE MPS WERE MORE TOXIC TO PLANT SEEDLINGS THAN POLYSTYRENE AND POLYPROPYLENE, CAUSING SIGNIFICANT OXIDATIVE STRESS. SIMILARLY, OXIDATIVE STRESS IMPACTS ON SOIL ORGANISMS WERE HIGHLIGHTED WHEN EXPOSED TO MPS AND PESTICIDES. RESEARCH IN THIS AREA IS EXPECTED TO CONTINUE GROWING, AIDING IN DELINEATING DISTINCT RESEARCH PATHS, PARTICULARLY FOCUSING ON OXIDATIVE STRESS, BIOACCUMULATION, AND HEAVY METALS. © 2024, KAUNO TECHNOLOGIJOS UNIVERSITETAS. ALL RIGHTS RESERVED.